A novel bacterium-like particles platform displaying antigens by new anchoring proteins induces efficacious immune responses - Niu, Lingdi; Gao, Mingchun; Ren, Hongkun; De, Xinqi; Jiang, Zhigang; Zhou, Xinyao; Liu, Runhang; Li, Hai; Duan, Haoyuan; Zhang, Chuankun; Wang, Fang; Ge, Junwei (Frontiers in Microbiology, 2024)
Bacterium-like particles (BLP) are the peptidoglycan skeleton particles of lactic acid bacteria, which have high safety, mucosal delivery efficiency, and adjuvant effect. It has been widely used in recent years in the development of vaccines. Existing anchoring proteins for BLP surfaces are few in number, so screening and characterization of new anchoring proteins are necessary. In this research, we created the OACD (C-terminal domain of Escherichia coli outer membrane protein A) to serve as an anchoring protein on the surface of BLP produced by the immunomodulatory bacteria Levilactobacillus brevis 23017. We used red fluorescent protein (RFP) to demonstrate the novel surface display system's effectiveness, stability, and ability to be adapted to a wide range of lactic acid bacteria. Furthermore, this study employed this surface display method to develop a novel vaccine (called COB17) by using the multi-epitope antigen of Clostridium perfringens as the model antigen. The vaccine can induce more than 50% protection rate against C. perfringens type A challenge in mice immunized with a single dose and has been tested through three routes. The vaccine yields protection rates of 75% for subcutaneous, 50% for intranasal, and 75% for oral immunization. Additionally, it elicits a strong mucosal immune response, markedly increasing levels of specific IgG, high-affinity IgG, specific IgA, and SIgA antibodies. Additionally, we used protein anchors (PA) and OACD simultaneous to show several antigens on the BLP surface. The discovery of novel BLP anchoring proteins may expand the possibilities for creating mucosal immunity subunit vaccines. Additionally, it may work in concert with PA to provide concepts for the creation of multivalent or multiple vaccines that may be used in clinical practice to treat complex illnesses.